The impact of workaholism on day-level workload and emotional exhaustion, and on longer-term job performance - Balducci, Cristian; Alessandri, Guido; Zaniboni, Sara; Avanzi, Lorenzo; Borgogni, Laura; Fraccaroli, Franco (Work and stress, 2021)
By drawing on effort-recovery theory, we conducted two studies to explore the short-term process through which workaholism may affect health and to assess the implications of such a process for job performance. In Study 1 we hypothesised that workaholic tendencies would affect daily workload and that daily workload would mediate the relationship between workaholic tendencies and daily emotional exhaustion. Data were provided by 102 workers consisting mostly of entrepreneurs, managers and self-employed individuals, who were followed for ten consecutive working days. Multilevel structural equation modelling, controlling for the general level of workload, neuroticism and conscientiousness, supported the hypotheses. Building on the results of Study 1, in Study 2 we hypothesised that workaholism would lead in the long run to a decline in job performance. Study 2 considered 519 employees of a large organisation and focused on their supervisors' performance ratings in two successive years. Workaholism was used to predict change in work performance. Work engagement was included in the model as a concurrent predictor of work performance. Contrary to what was hypothesised, workaholism did not affect performance; only work engagement did so, and in a positive way. The implications of the obtained results for further research on workaholism are discussed.